The don Juanito´s Mora vagues faces - Hilje Quirós, Luko (2018)
Even though every Costa Rican citizen believes that he or she has an exact idea of what Mr. Juanito Mora, liberator and national hero, looked like, a careful review of all the images depicting him—paintings, busts and statues—reveals that there have been distortions over time, thus altering some of his physiognomic aspects. This paper summarizes an analysis of these images and concludes that, in fact, the painting that served as a model for all of them was based on a photograph of unknown origin. This picture belongs to the personal archives of naval captain John M. Dow, stored in the University of Cornell library, in New York. Recently, it was found that this photograph was taken in Florence Charles Herbruger’s studio in Panama, in January 1860, a few months after Mora was overthrown as president of Costa Rica.